AN OVERVIEW OF PAST HISTORY BASED ON SEISMICITY PATTERN OF KASHMIR REGION, AN INTERPRETATION FROM 2005 EARTHQUAKE - A. Ghaffar; S. F. Abbas (Journal of Animal and Plant Sciences, 2010)
Kashmir region is one of the most seismic prone area lies on the Eurasian and Indian plate boundary. It has been the host of many great earthquakes from centuries including last 8th October 2005 earthquake. This study involves the seismicity pattern of Kashmir region before and after 8th October 2005 earthquake. Although the spatial and temporal seismicity patterns in an earthquake-prone Kashmir region are closely related to both tectonic regime and fault structures. It is the most difficult to quantify the relations in a way which allows large events in the seismic region to be predicted. However, regular and persistent studies regarding seismic activities are most important phenomena for the future recurrence and magnitude of earthquakes.  Seismicity time properties of Kashmir region are investigated through a systematic pattern recognition analysis. Statistical methods have been applied to a long time database of instrumental data recorded from 1904 – 2006. The seismicity pattern of this region reveals that this activity remains    very high just after earthquake and continues till 31st December 2006 after that it calm down. It also shows the comparison of seismicity pattern that are high from 8th October 2005 to 31st December 2005 while shows lessened trend afterwards during the year 2006. The purpose of this study was to determine the future strain buildup, uplift rates, slip rates, recurrence intervals, and seismicity along different faults needed to be monitored continuously to avoid major human disaster like the 8th October 2005 Muzaffarabad earthquake, in the Kashmir region.
Keywords: Seismicity pattern; statistical analysis; earthquake and Kashmir region